Exchange rate undervaluation and economic growth: Díaz Alejandro (1965) revisited - Gluzmann, Pablo Alfredo (2012)
To understand the growth effects of currency undervaluation we estimate its impact on the different components of GDP. We find that, for developing countries, undervaluation does not affect the tradable sector, but does lead to greater domestic savings and investment, as well as employment.